Food Security in Remote Disaster-Prone Prisons: a Case Study of Nusakambangan as an Integrative Model of Disaster Resilience and Prisoner Rehabilitation - Suryanto, Heru; Sudarno, Kurnia Agung; Setiawibawa, Rachmat; Syahtaria, Moh Ikhwan; Uksan, Arifuddin (Cita konsultindo, 2025)
This research focuses on analyzing food security in remote prisons that are potentially vulnerable to disasters, with a case study focus on Nusakambangan Island, Central Java. The issue of food security in correctional environments is important because Nusakambangan's isolated geographical conditions cause complete dependence on external logistics supplies, especially from sea routes. When extreme weather, emergency conditions or disasters occur, food distribution is often disrupted, so internal production strategies are needed to maintain supply continuity. This research uses a descriptive qualitative approach with a case study method and analyzes field data from several prisons on Nusakambangan, including the Open Prison, Nirbaya, Gladakan, Kembang Kuning, Karanganyar, and Pasir Putih.The research findings indicate that the development of agricultural, livestock, and fisheries activities on Nusakambangan serves a dual role: as a food security strategy and as a means of inmate rehabilitation. The Open Prison and Kembang Kuning Prison are the most advanced models of food diversification with various commodities, while Nirbaya Prison demonstrates innovative adaptation to rocky land through a terracing system. This research concludes that food security on Nusakambangan can serve as an integrative model between correctional policies and adaptive food systems. Key recommendations include the establishment of an integrated food management institution, increased cross-ministerial technical support, and the development of a sustainable storage system and training for inmates. With institutional strengthening and agricultural innovation, Nusakambangan has the potential to become a national laboratory for resilient, productive, and equitable correctional food security.